Pengaruh Metode Demonstrasi terhadap Kemampuan Interaksi Sosial pada Anak Kelompok B di TK Negeri Lebiti, Kecamatan Togean, Kabupaten Tojo Una-Una, Sulawesi Tengah - Nurhijrah Ladiku; Nunung Suryana Jamin; Sulastya Ningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study was conducted at TK Negeri Lebiti, Togean District, Tojo Una-una Regency, Central Sulawesi, with the aim of determining the effect of the demonstration method on the social interaction skills of early childhood students. The background of this research is based on the importance of developing children’s social abilities from an early age through learning activities that involve direct participation and interaction. The main problem examined in this study is whether the demonstration method significantly influences the improvement of children’s social interaction skills. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of two classes of children aged 4–6 years, comprising 12 children in the experimental class and 20 children in the control class, making a total of 32 participants. The experimental class was taught using the demonstration method, while the control class used conventional learning methods. Data were collected through observation and assessment of children’s social behaviors during learning activities. The collected data were analyzed using statistical techniques to test the research hypothesis. The findings are expected to provide empirical evidence regarding the effectiveness of the demonstration method in improving children’s social interaction skills within the context of early childhood education.